An Audacious Voyage during COVID-19 Pandemic in Management of Patients with Aneurysmal Subarachnoid Hemorrhage at Tertiary Neurological Center in Nepal - Rajbhandari, Pravesh; Kumar Yadav, Jayant; Giri, Shilpa; Shrestha, Bishal; Kayastha, Jessica; Shrestha, Janam; Nepal, Gopi; Rajbhandari, Reema; Gurung, Pritam; Shrestha, Jitesh; Palikhe, Anusha; Bahadur Karki, Shambhu; et al. (Annapurna Journal of Health Sciences, 2022)
Introduction: Aneurysmal Subarachnoid Hemorrhage (SAH) is a neurosurgical emergency for which testing for COVID PCR was not an option and was unlikely to change the management of the case. Hence, all surgeries were performed without COVID PCR and Rapid Diagnostic Test (RDT) at our center for the welfare of the patient despite risks involved for the surgeons and supporting staff. Methods: Data were collected retrospectively of all cerebral aneurysm patients who received treatment at Annapurna Neurological Institute and Allied Sciences during the covid pandemic between February 2020 to May 2021. Their demographic profile, clinical and imaging characteristics, treatment decision, postoperative complication, postoperative functional status in terms of Modified Rankin Scale were taken into consideration and analyzed. Result: 63 patients were enrolled in study with patient age ranging from 9 years to 81 years. Male to female ratio was 1:3. Amongst them, 28% had hypertension. 82% underwent microsurgical clipping while three patients underwent coiling. Basilar Top aneurysm, Para clinoid aneurysm, PICA aneurysm underwent simple coiling. Wrapping, bypass and trapping were performed in 1, 1, and 3 cases respectively. At the time of discharge, most of the patients (77%) achieved good functional recovery (mRS ≤ 2) while mortality was reported in 8% of patients. Based on our experience and limited dataset, posterior location of aneurysm, increasing Hunt[1]Hess Grade and modified fisher grade had poor prognosis, related with degree of cerebral vasospasm, and delayed cerebral ischemia. Conclusion: Results from our study showed outcomes in surgical patients with aneurysmal SAH at par with international standards. COVID pandemic although posed initial difficulties, with proper guidelines and protocols in place, we were able to perform the emergency surgeries without compromising our standards.